Numerical Study of Turbulent Porous Media Combustion Coupled with Thermoelectric Generation in a Recuperative Reactor - Henriquez-Vargas, L; Donoso-Garcia, P (Elsevier Ltd, 2015)
This paper presents two-dimensional simulations of an adiabatic recuperative porous media burner in turbulent regime coupled with thermoelectric elements. Time and volume averaged transport equations and second order turbulence model were employed. FLUENT was used to simulate the reactor through its UDF (User Defined Functions) and UDS (User Defined Scalars) interfaces for extra terms involving turbulence and thermoelectric quantities. The study includes the production of thermal NOx modeled by the extended Zeldovich mechanism with postprocessing computation. Flow and electric field computations were obtained considering as variables gas inlet velocity and composition, porous media thermal conductivity and inner wall insulation material. Flammability limits for stable combustion were found alongside with the electric potential generated within the system. Higher values of electrical potential, thermoelectric efficiency and flame temperatures were reached when the gas mixture energy content and heat recovery capacity of the system were increased. © 2015 Elsevier Ltd.